P4_14 My God Its Full of Star(s) - Hague, Peter; Davis, Claire; Tilley, Fred (Physics Special Topics, 2011)
<!– /* Font Definitions */ @font-face font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:auto; mso-font-pitch:variable; mso-font-signature:3 0 0 0 1 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> A Dyson sphere is any hypothetical structure designed, by a very advanced civilisation, to capture all or almost all of the output of a star as useful energy. One simple configuration is a symmetric spherical shell, but this structure will not be kept in place by the star’s gravity. This paper investigates if it can be kept in place by radiation pressure, but finds that without a system of active control to regulate how much momentum the solar radiation imparts to the sphere, it cannot be made stable through light pressure alone.